Governing Indonesia’s Secondary Education System: Challenges and Opportunities for Improvement in the Province of Yogyakarta - Astrid Meilasari Sugiana; Jumintono Jumintono (Proceeding of International Conference on Islamic Education, 2016)
This paper focuses on government policies for improving secondary education in decentralized Indonesia. The research combines policy evaluation in the field of education through mixed methods, namely the top down method measuring the effectiveness of Indonesia’s policy reforms in numerical terms and the bottom up ethno-methodological approach incorporating soft system methodology for complementing policy evaluation. Data analysis was done by examining the distribution of narratives provided by the respondents and carrying out a thematic analysis in which emerging themes were used to produce a complex and coherent narrative of the discourse emerging from the case study site in Yogyakarta Province, Indonesia. The education system in modern Indonesia is marked by the tension between the centralized policy strategy of the Suharto period and the reactive strategy of Post-Suharto decentralization. During his current administration, President Joko Widodo promulgated education policies focusing on basic education reforms in five major areas, namely (i) facilitating the expansion of education facilities across Indonesia through the public and private sector (expansion of facilities and infrastructure in terms of quantity and quality), (ii) making basic education more affordable and accessible across regions and social-economic indicators (accessibility), (iii) improving the quality of educators, service and outputs in basic education (quality), (iv) increasing the relevance of basic education to the demands of tertiary education, the labor market and local economic development (relevance), and (v) good governance and accountability of Indonesia’s basic education system (accountability and public responsiveness). In conjunction with the government and the market in education, indigenous social and political groups have played significant roles in developing the secondary education system in Indonesia. Moreover, these groups have also improved pupils’ performance and pupils’ learning outcomes by improving the extent and quality of the services they provide in comparison to those provided by public schools run by the government. Individualized services which cater to the needs, backgrounds and interests of the consumers have had profound impacts on enrollment, retention, motivation and pupils’ character, knowledge, technical competence and competitiveness. This makes the education system more engaging, empowering and inclusive while taking into account its comprehensiveness. This also aids in promoting learning communities for complementing the government induced education system, for protecting children and for providing a holistic and integrated education services.